Aplikasi Pencatatan Keuangan Berbasis Website Dengan Metode Rapid Application Development Pada PT Samsriwi Adi Megah - Apisca, Dhea; Surojudin, Nurhadi; ., Edora (Prodi Sistem Informasi Universitas Dharma Andalas, 2024)
In an increasingly competitive and rapidly changing business world, keeping company finances organized and transparent is key to success. The website-based financial recording application comes as a modern solution that provides convenience and efficiency in managing the Company's finances. PT Samsriwi Adi Megah is one of the garment companies. It was found that financial record management still relies on the Microsoft Office Excel application so that it experiences searching for data within a certain period of time. This is because financial data is stored in many Excel worksheets or separate files. To overcome these problems, companies need to develop a website-based financial recording application with the rapid application development method. With an integrated system, the Company can accelerate the data processing process, facilitate report making and improve the right decision making. The application of financial recording applications can improve the efficiency of PT Samsriwi Adi Megah's financial data processing and provide accurate and fast information.